Development of Straight Line Robot Movement Using Digital Compas Module - Wan Ismail, Ibrahim; Mohd Riduwan, Ghazali; Mohd Zaidi, Mohd Tumari (2012)
This project focuses on the development of straight line movement for a four-wheeled mobile robot. In this project, a DC gear motor is chosen as motion control for two driving wheels and the direction of robot will be controlled by servo motor to two steering wheels. PIC is selected as the brain board controller due to react and respond to the data received from Digital Compass Module to identify and figure out desired position. The implementation of internal PID algorithm is essentially used to restore the system to desired set-point position. Application of Digital Compass Module with the aid of PID control algorithm may command to drive the servo motor to go towards in straight line platform in accordance to the desired set-point direction has been fixed. The robotic hardware has been developed and analyzed successfully. As a result, in despite of unexpected external force varying the desired direction of robot, the robot would still be able to veer back to the original set-point direction to achieve a smooth and stabilized straight line movement.